Pengembangan Media Pembelajaran Biologi Menggunakan Aplikasi Camtasia - sari, indah karunia; Tanjung, Indayana Febriani; Adlini, Miza Nina (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the validity, practicality, and effectiveness of biology learning media using the Camtasia application which was developed in the form of learning videos on the subject of the human circulatory system. This study uses the Research and Development (R&D) method, with the ADDIE model namely analysis, design, development, implementation, and evaluation. The instruments used were media and material expert validation sheets, teacher and student response questionnaires, and multiple choice tests to assess student effectiveness. The developed media has an average overall media validity score of 0.83 which indicates that it meets the valid criteria. It is said to be